Measuring CO2 emissions level for more sustainable distribution in a supply chain - Dubisz, Damian; Golińska-Dawson, Paulina; Koliński, Adam (Engineering and Applied Science Research, 2022)
The stakeholders put pressure on supply chain managers to provide the performance which is economically viable and also environmentally sound. The inclusion of environmental factors in the set of periodically measured KPIs, such as the carbon dioxide equivalent (CO2e) becomes more crucial. The aim of this paper is to identify the challenges, which appear when measuring the carbon footprint in a supply chain. The emphasis is put on the direct emissions from distribution operations in terms of European perspective. Through literature review and two case studies conducted in the retailing companies we identify the factors which influence the CO2 in the area of distribution in a supply chain. The result of the conducted research is of great importance for the creation of more sustainable and green distribution supply chains (GrSC). On the basis of surveys conducted among transport managers, the main factors determining the emissivity of the supply chain have been shown. Also the main challenges faced enterprises that want to measure and manage their carbon footprint of distribution processes were identified. The main contribution of this paper is to provide an actionable set of variables which shall be included by supply chain managers in their decision-making process in order to make the distribution operations more sustainable.